Effect of Oxygen on Lactose Metabolism in Lactic Streptococci - Smart, John B. (1987)
Three strains of Streptococcus lactis, two of Streptococcus cremoris, and one of Streptococcus thermophilus metabolized oxygen in the presence of added carbohydrate primarily via a closely coupled NADH oxidase/NADH peroxidase system. No buildup of the toxic intermediate H(2)O(2) was detected with the three S. lactis strains. All six strains contained significant superoxide dismutase activity and are clearly aerotolerant. Lactose- or glucose-driven oxygen consumption was biphasic, with a rapid initial rate followed by a slower secondary rate which correlated with factors affecting the in vivo activation of lactate dehydrogenase. The rate of oxygen consumption was rapid under conditions that led to a reduction in lactate dehydrogenase activity (low intracellular fructose 1,6-bisphosphate concentration). These conditions could be achieved with nongrowing cells by adding lactose at a constant but limiting rate. When the rate of lactose fermentation was limited to 5% of its maximum, nongrowing cells of S. lactis strains ML3 and ML8 carried out an essentially homoacetic fermentation under aerobic conditions. These same cells carried out the expected homolactic fermentation when presented with excess lactose under anaerobic conditions. Homoacetic fermentation leads to the generation of more energy, by substrate-level phosphorylation via acetate kinase, than the homolactic fermentation. However, it was not observed in growing cells and was restricted to slow fermentation rates with nongrowing cells.